1986
DOI: 10.1126/science.3006248
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Vasopressin Action by Atrial Natriuretic Factor

Abstract: Atrial natriuretic factor results in diuresis in animals and humans, perhaps because atrial natriuretic factor increases renal blood flow. The possibility that this diuresis is due to direct inhibition of renal tubular epithelial water transport was examined in rabbit collecting tubules perfused in vitro. Atriopeptin III inhibition of the hydraulic conductivity response to the hormone arginine vasopressin but not to either 3'5'-cyclic adenosine monophosphate or forskolin was found. These results suggest that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
2
3

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(68 citation statements)
references
References 13 publications
3
60
2
3
Order By: Relevance
“…However, the effect of ANP (through an increase in cGMP) on sodium and fluid transport in the collecting duct is still controversial. Some earlier studies showed that it decreases both sodium reabsorption and vasopressin-induced water transport in collecting ducts (Dillingham and Anderson, 1986;Nonoguchi et al, 1988;Nonoguchi et al, 1989), whereas later studies do not confirm these inhibitory effects (Bouley et al, 2000;Rouch et al, 1991). This might probably due to the fact that ANP has a biphasic effects on renal water reabsorption process.…”
Section: Atrial Natriuretic Peptide (Anp)contrasting
confidence: 41%
“…However, the effect of ANP (through an increase in cGMP) on sodium and fluid transport in the collecting duct is still controversial. Some earlier studies showed that it decreases both sodium reabsorption and vasopressin-induced water transport in collecting ducts (Dillingham and Anderson, 1986;Nonoguchi et al, 1988;Nonoguchi et al, 1989), whereas later studies do not confirm these inhibitory effects (Bouley et al, 2000;Rouch et al, 1991). This might probably due to the fact that ANP has a biphasic effects on renal water reabsorption process.…”
Section: Atrial Natriuretic Peptide (Anp)contrasting
confidence: 41%
“…These divergent results may be due to strain differences. Nevertheless, because urine flow increased with ANP infusion in young animals in both studies, there may be age-related changes in direct ANP-mediated inhibition of vasopressin action on the tubule (23).…”
Section: Discussionmentioning
confidence: 99%
“…First, it is possible that the increased plasma ANH levels that further increased during water load in þMCE patients, inhibited the effect of relatively high AVP levels on urinary osmolality (21)(22)(23). Secondly, the inhibitory effect of high plasma concentrations of ANH on tubular sodium reabsorption and an ANH-induced increase in medullary blood flow in þMCE patients may have had an effect on the medullary osmotic gradient between interstitial fluid and the lumen of the collecting duct.…”
Section: Discussionmentioning
confidence: 99%